On Generalized Strongly p-Convex Functions of Higher Order - Muhammad Shoaib Saleem; Yu-Ming Chu; Nazia Jahangir; Huma Akhtar; Chahn Yong Jung (Journal of Mathematics)
The aim of this paper is to introduce the definition of a generalized strongly p-convex function for higher order. We will develop some basic results related to generalized strongly p-convex function of higher order. Moreover, we will develop Hermite–Hadamard-, Fejér-, and Schur-type inequalities for this generalization.